In vitro cytotoxicity, genotoxicity and apoptoxicity of 8-hydroxy-3,6-disulphonaphthyl azohydroxynaphthalenes using Human Lymphocytes: Experimental and theoretical profiling (2023)
Regulatory agencies require demonstration of non-genotoxicity of new chemical entities prior to their use as pharmaceuticals or additives. Consequently, the in vitro cytotoxicity, genotoxicity and apoptoxicity of five novel monoazo colourants (8-hydroxy-3,6-disulphonaphthyl azohydroxynaphthalenes, 3a-e) on human lymphocytes were evaluated using a cell viability assay, alkaline comet assay, DNA diffusion assay, DFT calculations and molecular docking. The test concentrations of the compounds varied from 0 to 3.4 mM. Relative to negative control, the compounds at concentrations up to 0.5mM induced small dose-dependent reduction (< 20%) in viability of lymphocytes. Statistically significant changes (p<0.05) in DNA damage parameters (percent tail DNA, tail extent moment, olive tail moment) were observed at all concentrations of 3a, 3b while 3c-e showed genotoxicity at 2.8, 0.17 and 3.4 mM respectively. Compounds 3a, 3b, 3d induced apoptosis at concentrations below cytotoxic doses while 3c and 3e were non-apoptoxic at all test concentrations. DFT calculations showed the genotoxicity of 3a-e increased with electrophilicity and ionization potentials of the compounds. Molecular docking of 3a-e with apoptosis-associated proteins revealed binding affinity patterns that were consistent with observed experimental apoptoxicity. The structure-genotoxicity relationships of five novel monoazo compounds, which can be employed in the design of safer congeners, have been elucidated.